CLINICAL-EVALUATION OF LOW-DOSE INTRADERMALLY ADMINISTERED HEPATITIS-B VACCINE - A COMPARISON OF PLASMA-DERIVED AND RECOMBINANT YEAST-DERIVED VACCINES - (:unkn) unknown (BUTTERWORTH-HEINEMANN LTD, 1992)
A study of the safety and immunogenicity of plasma-derived and yeast-derived recombinant hepatitis B vaccines administered by the intradermal route is reported. Three groups of medical students were inoculated intradermally at 0, 1 and 6 months with 2-mu-g of vaccine. Group 1 (n = 24) were administered plasma-derived vaccine (Green Cross HB-vaccine), group 2 (n = 21) yeast-derived recombinant vaccine (Engerix B), and group 3 (n = 13) two doses of plasma-derived vaccine with a third dose of yeast-derived vaccine. One month after administration of the third dose of vaccine, seroconversion rates in each of the three groups were 83, 100 and 92%, respectively, with anti-HBs geometric mean titres (GMT) of 329 IU l-1, 1390 IU l-1 and 1061 IU l-1. Although differences in seroconversion rates were not statistically significant, the GMT in group 1 was significantly lower than that in group 2 (p < 0.01) and group 3 (p < 0.05). The results presented show that intradermal administration of plasma-derived or yeast-derived vaccine, or a combination of the two, can provoke an effective immunogenic response to hepatitis B virus at approximately 10% of the cost of intramuscular vaccination. In this study administration of yeast-derived vaccine yielded better results than plasma-derived vaccine when administered by the intradermal route.
Keywords: HEPATITIS-B; VACCINE; PLASMA-DERIVED; YEAST-DERIVED; INTRADERMAL; VIRUS-VACCINE; IMMUNOGENICITY; ADULTS